Is Financial Development a Determinant of Tourism? A Case of Selected Emerging Markets - Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2022)
This paper examined the influence of financial development on tourism growth in selected emerging markets with the aid of panel data (2001-2019). The influence of the combination between financial and development of human capital on tourism growth in selected emerging markets was also investigated. Fully modified ordinary least squares (FMOLS), fixed effects, pooled ordinary least squares (OLS) and the random effects were the econometric estimation methods employed in this study. In a nutshell, factors such as financial sector development, foreign direct investment, trade openness, development of human capital and economic growth and the complementarity variable had a significant positive influence on tourism growth in selected emerging markets. To enhance tourism growth, selected emerging markets are urged to design and implement policies and programmes earmarked at increasing financial development, foreign direct investment, trade openness, economic growth and development of human capital. Threshold panel regression analysis could be another avenue through which the influence of financial development on tourism is examined in future.